Comparison of lower-body neuromuscular performance profiles between 100 m and 400 m Olympic sprinters - Cabarkapa, D.; Batra, A.; Cabarkapa, D. V.; Fry, A. C. (Frontiers in Sports and Active Living, 2025)
The purpose of the present study was to examine and compare the lower-body neuromuscular performance characteristics of Olympic-level 100 m and 400 m sprinters. Following a standardized warm-up procedure, fourteen professional female athletes completed three countermovement vertical jumps with no arm swing, while standing on a uni-axial force plate system sampling at 1,000 Hz. Force-time metrics, expressed both in absolute (A) and relative (R) terms, were analyzed across braking (eccentric) and propulsive (concentric) phases of the jumping motion, including inter-limb asymmetry measures. Independent t-tests or Mann-Whitney U tests were used to examine between-group statistically significant differences (p < 0.05). The results reveal that 100 m sprinters tend to display greater force and power-producing capabilities than their 400 m counterparts. Specifically, average braking power (A: 1,212.3 vs. 1,052.9 W), average propulsive power (A: 2,343.8 vs. 2,026.9 W), peak propulsive power (A: 4,030.1 vs. 3,503.5 W; R: 64.1 vs. 59.4 W·kg-1), average propulsive velocity (1.79 vs. 1.69 m·s-1), peak propulsive velocity (3.13 vs. 2.93 m·s-1), and jump height (47.8 vs. 41.4 cm) were all greater in 100 m than 400 m sprinters. In addition, average and peak braking and propulsive force inter-limb asymmetries remained below 10% in both groups, with no significant differences being observed. Therefore, these findings suggest that 100 m sprinters may benefit from training regimens focused on the development of force and power-producing capabilities, particularly through exercises that enhance the propulsive (concentric) phase of the movement, while 400 m sprinters may benefit from a more integrated training approach, focused on balancing speed development with strength-endurance components.